1988
DOI: 10.1111/j.1472-765x.1988.tb01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: an improved method for differential staining of Bacillus thuringiensis crystals

Abstract: A new staining method is described using naphthalene black 12B and Gurr's improved R66 Giemsa for staining all known crystal types produced by Bacillus thuringiensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Preliminary screening based on colony morphology was carried out for Bt‐like colonies (Wigley et al, 2005) after 4 days and the presence of the Bt marker was confirmed using stained bacterial smears prepared as described by Chilcott & Wigley (1988). A speck of each colony was removed from the plate, smeared on to a glass slide, air‐dried, and baked at 100 °C for 1 h. The slide was dipped in 1.5% (wt/vol) naphthalene black (BDH Laboratories, Poole, UK) in 37% acetic acid for 2 min, rinsed in water, and stained in 2% (vol/vol) Gurr’s Improved R66 Giemsa stain solution for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary screening based on colony morphology was carried out for Bt‐like colonies (Wigley et al, 2005) after 4 days and the presence of the Bt marker was confirmed using stained bacterial smears prepared as described by Chilcott & Wigley (1988). A speck of each colony was removed from the plate, smeared on to a glass slide, air‐dried, and baked at 100 °C for 1 h. The slide was dipped in 1.5% (wt/vol) naphthalene black (BDH Laboratories, Poole, UK) in 37% acetic acid for 2 min, rinsed in water, and stained in 2% (vol/vol) Gurr’s Improved R66 Giemsa stain solution for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…The colonies resembling Bt cream-colored and have the appearance of a fried egg on a plate were selected and gram stained, sub-cultured as ribbon streak four colonies per plate on T 3 agar medium tryptone-3 g, tryptose-2 g, yeast extract-1.5 g, sodium phosphate-0.05 M, manganese chloride-0.005 g, agar-15 g, distilled water-1000 mL, pH-6.8 . After 72 h of incubation crystal staining was done Chilcott and Wigley, 1988 . The isolates showing the presence of crystalline inclusions were selected as Bt and streaked on T 3 agar medium for single colony purification. Broth culture was made from the isolated single colonies of crystal positive Bt isolates.…”
Section: Consistency Of Tree Was Checked By a Bootstrap Valuementioning
confidence: 99%
“…Preliminary screening based on colony morphology was carried out for Bt-like colonies after 4 days and confirmatory evidence of presence of the Bt marker was sought using stained bacterial smears prepared as described by Chilcott & Wigley (1988). A speck of the colony was removed from the plate using a sterile toothpick, smeared onto a water droplet placed on a glass slide, allowed to air-dry and baked at 100°C for 1 h. The slide, while still hot, was dipped in 1.5% naphthalene black (BDH Laboratories) in 37% acetic acid for 2 min, rinsed in water, and stained in 2% Giemsa stain for 2 min.…”
Section: Laboratorymentioning
confidence: 99%